Hepatotoxicity in patients treated according to the nephroblastoma trial and study SIOP-9/GPOH - Ludwig, Rolf; Weirich, Angela; Abel, Ulrich; Hofmann, Walter; Graf, Norbert; Tournade, Marie‐France (Medical and pediatric oncology, 1999)
BACKGROUND: A major problem for children receiving Wilms tumor (WT) chemotherapy is hepatotoxicity, which may even be life-threatening. Dactinomycin (AMD) has been shown to be an important factor, as has abdominal irradiation. PROCEDURE: In the nephroblastoma trial and study SIOP-9 (SIOP-9) two different regimens for the application of AMD were used (standard dose over 3-5 days vs. double dose on a single day). In children at increased risk for local relapse, postoperative abdominal irradiation was given. We analyzed the influence of AMD and radiotherapy on the development of hepatotoxicity in 481 children treated in centers of the German Paediatric Oncology and Haematology Society (GPOH). A special questionaire was sent out for all patients with reduced treatment or delay of more than 1 week because of hepatotoxicity. Because SIOP and the National Wilms Tumor Study (NWTS) used different criteria to asses hepatotoxicity,we applied both definitions. RESULTS: All 72 cases of mild or severe hepatotoxicity occurred during treatment with AMD over 3-5 days with the standard dose (9.4-22.5 microgram/kg/week) compared to none in the group receiving a double dose on 1 day (3.75-8 microgram/kg/week; P < 0.001). Irradiation of the right abdomen, including parts of the liver, enhanced liver toxicity significantly, with a relative risk (RR) of 2.6 (P < 0.003). Preoperative liver toxicity was more frequent in smaller children (P = 0.02) and especially if no dose reduction was done in children with body weight of less than 12 kg (RR 5.3, P = 0.01). If severe liver toxicity was defined according to NWTS criteria, 10% of all treated patients were affected compared to 4.8% if McDonald's criteria for hepatic veno-occlusive disease (VOD) were applied. CONCLUSIONS: To diminish the hepatotoxicity of WT treatment, AMD dose intensity should be reduced (below 10 microgram/kg per week), especially in smaller children or when the liver is irradiated.